Strategic Global HR Planning and Competency Development in Multinational Corporations: A Systematic Review Using Prisma 2020 - Insan, Muhammad Yalzamul; Onom, Jojor; Aryanti, Meilisa; Dalimunthe, Ritha F; Lumbanraja, Prihatin (Jurnal Ekonomi dan Bisnis Digital, 2025)
The integration of global HR planning and competency development serves as a strategic key for multinational corporations (MNCs) in navigating the dynamics of the global market. However, the complexities of culture, legal frameworks, and organizational structures across countries pose challenges to its implementation. This study aims to systematically review literature on the integration of global HR planning and competency development in MNCs, identifying challenges, strategies, and best practices. Following the PRISMA 2020 guidelines, a literature search was conducted across Scopus, Web of Science, and EBSCOhost databases for publications between 2010 and 2024. A qualitative analysis was performed on 32 articles meeting the inclusion criteria. Key findings highlight: (1) the importance of adapting HR strategies to local contexts without compromising global consistency; (2) the critical role of HR professionals as bridges between global strategy and local needs; and (3) competency-based approaches as tools to align business goals with individual development. Effective integration of global HR planning and competency development requires a holistic approach that considers internal and external factors, as well as flexibility in responding to global dynamics.